SECURING FINANCIAL INSTITUTIONS: SAFEGUARDING GUARANTEES AMID STATE CONFISCATION - Zulfikri Zulfikri; Febri Erdin Simamora; Zulkarnaini Zulkarnaini (Universitas Syiah Kuala, 2023)
This study explores the intricate legal landscape surrounding the safeguarding of financing institutions when the assets serving as guarantee material are confiscated by the state. The examination delves into the complexities, challenges, and mechanisms available to protect the interests of these financial entities when their collateral is seized. By scrutinizing legal frameworks, case studies, and pertinent regulations, the paper aims to elucidate potential avenues for mitigating risks and securing the rights of financing institutions amidst state asset confiscation. The analysis presents a comprehensive overview of the legal protections available to these institutions, offering insights into potential measures and strategies to fortify their position in such scenarios.